Fluctuating salience in those living with genetic risk of motor neuron disease: A qualitative interview study - Jade Howard; Fadhila Mazanderani; Karen Forrest Keenan; Martin R. Turner; Louise Locock (Health Expectations, 2024)
Abstract Background Motor neuron disease (MND) (also known as amyotrophic lateral sclerosis) is a life‐limiting neurodegenerative condition. In up to 20% of people with MND, a pathogenic variant associated with autosomal dominant inheritance can be identified. Children of people carrying a pathogenic variant have a 50% chance of inheriting this and a higher, although harder to predict, chance of developing the disease compared to the general adult population. This paper explores the experience of living with the genetic risk of MND. Methods We undertook a UK‐based interview study with 35 individuals, including: 7 people living with genetically‐mediated forms of MND; 24 asymptomatic relatives, the majority of whom had an increased risk of developing the disease; and 4 unrelated partners. Results We explore how individuals make sense of genetic risk, unpacking the interplay between genetic knowledge, personal perception, experiences of the disease in the family, age and life stage and the implications that living with risk has for different aspects of their lives. We balance an emphasis on the emotional and psychological impact described by participants, with a recognition that the salience of risk fluctuates over time. Furthermore, we highlight the diverse strategies and approaches people employ to live well in the face of uncertainty and the complex ways they engage with the possibility of developing symptoms in the future. Finally, we outline the need for open‐ended, tailored support and information provision. Conclusions Drawing on wider literature on genetic risk, we foreground how knowledge of MND risk can disrupt individuals' taken‐for‐granted assumptions on life and perceptions of the future, but also its contextuality, whereby its relevance becomes more prominent at critical junctures. This research has been used in the development of a public‐facing resource on the healthtalk.org website. Patient or Public Contribution People with experience of living with genetic risk were involved throughout the design and conduct of the study and advised on aspects including the topic guide, sampling and recruitment and the developing analysis. Two patient and public involvement contributors joined a formal advisory panel.